IMPROVING ENGLISH VOCABULARY THROUGH MAGIC BOX GAME FOR YOUNG PEOPLE WHO DROP OUT OF SCHOOL IN HABI VILLAGE - Genoveva Dua Eni (Academic Journal of Educational Sciences, 2022)
The purposes of this research are to find out how the young people who drop out of school in Habi Village improve their English vocabulary through magic box games and to find out the problems of young people who drop out of school in Habi Village in improving English vocabulary through magic box game. This research was action research. This research was conducted in Habi Village. The subjects in this research were young people who drop out of school which consist of 12 people. In collecting the data, the researcher used written interviews and tests. The result of the research showed that there are several problems faced by the learners, namely lack of vocabulary, some of them could easily follow the writing exercises but some still confronted difficulties in doing exercises, and they did not choose the appropriate words. The total mean score of the learner’s results on the pre-test and post-test was 7.75. The researcher concluded that using magic box games in learning could improve the English vocabulary of young people who drop out of school in Habi Village.